2014
DOI: 10.1111/jmp.12108
|View full text |Cite
|
Sign up to set email alerts
|

Dilated cardiomyopathy in a De Brazza's monkey (Cercopithecus neglectus)

Abstract: Necropsy revealed pulmonary infarction, subsequent to heart failure from dilated cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…However, there are few studies on wild animals using VHS as a diagnostic tool. Felkai et al (2014) described the presence of residual pleural effusion, heart increase and cardiomegaly, associated to increases in the VHS values in Cercopithecus neglectus, confirmed later by echocardiographic examination. The VHS values found in our assessments (mean 9.25±0.32v, between males and females) were similar to those assessed for the Callithrix jacchus (9.42±0.44v), described by Wagner & Kirberger (2005).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, there are few studies on wild animals using VHS as a diagnostic tool. Felkai et al (2014) described the presence of residual pleural effusion, heart increase and cardiomegaly, associated to increases in the VHS values in Cercopithecus neglectus, confirmed later by echocardiographic examination. The VHS values found in our assessments (mean 9.25±0.32v, between males and females) were similar to those assessed for the Callithrix jacchus (9.42±0.44v), described by Wagner & Kirberger (2005).…”
Section: Discussionmentioning
confidence: 78%
“…These reference data are scarce for nonhuman primates. Only Felkai et al (2014) describe a CTR of 0.68 (68%) for Cercopithecus neglectus with an acquired heart disease associated to 7-10% fractional shortening. In our studies, we observed strong interaction between the VHS and CTR values (y = 0.1069x -0.4346. r=0.78), a relationship that has not yet been discussed in the literature for nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
“…Felkai et al . described the presence of residual pleural effusion, enlargement of the heart and cardiomegaly, associated with increases in VHS values in Cercopithecus neglectus , later confirmed by echocardiographic examination.…”
Section: Discussionmentioning
confidence: 91%
“…This situation is similar to what happens with the different breeds of dogs, 10,14,16 also in other primates, such as vervet monkeys. 17 Felkai et al 18 DV, dorsoventral incidence; LLL, laterolateral left incidence; LLR, Laterolateral right incidence; VD, ventrodorsal incidence. "A" indicates that there is no statistical difference in the same column, and "a" indicates that there is no statistical difference on the same row.…”
Section: Discussionmentioning
confidence: 99%
“…Published data dealing with CTR measurements in non-human primates are rather scarce. The species Cercopithecus neglectus has been reported to have a CTR value of 0.68; however, these have recorded the incidence of heart disease (13) . When the CTR data found in HNP are compared with that of humans, it is evident that values higher than 0.55 are already accepted to be indicative of cardiomegaly (14) .…”
Section: Resultsmentioning
confidence: 99%